Ultrasound of the Musculoskeletal System - Bianchi, Stefano; Martinoli, Carlo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
This book is a comprehensive reference and practical guide on the technology and application of ultrasound to the musculoskeletal system. It is organized into two main sections. The first is devoted to general aspects, while the second provides a systematic overview of the applications of musculoskeletal ultrasound in different areas of the body. Additional sections address instrumentation, interventional procedures, and pediatric applications. Each chapter of the second main section provides an introduction on clinical anatomy and the essentials of clinical history and physical examination. Thereafter, performance of the ultrasound study is explained and the normal and pathological anatomy is reviewed. To assist in understanding, the ultrasound scans are correlated with drawings, photographs, images obtained using other modalities, and anatomic specimens. There is a generous complement of high-quality illustrations based on high-end equipment. This book will acquaint beginners with the basics of musculoskeletal ultrasound, while more advanced sonologists and sonographers will learn new skills, means of avoiding pitfalls, and ways of effectively relating the ultrasound study to the clinical background.
Instrumentation: Technical Requirements (Derchi/Rizzatto) -- General: Skin/Subcutaneous Tissue (Valle/Zamorani) -- Muscle and Tendon (Zamorani/Valle ) -- Nerve and Vessels (Valle/Zamorani) -- Bone and Joint (Zamorani/Valle) -- Individual Anatomic Sites: Upper Limb: Shoulder (Bianchi/Martinoli) -- Arm (Martinoli/Bianchi ) -- Elbow (Bianchi/Martinoli) -- Forearm (Martinoli/Bianchi ) -- Wrist (Bianchi/ Martinoli) -- Hand (Martinoli/Bianchi ) -- Lower Limb: Hip (Martinoli/Bianchi) -- Thigh (Bianchi/Martinoli) -- Knee (Martinoli/Bianchi) -- Leg (Bianchi/Martinoli) -- Ankle (Martinoli/Bianchi) -- Foot (Bianchi/Martinoli) -- Interventional Procedures: US-guided Interventional Procedures in the Musculoskeletal System (Bianchi/Zamorani) -- Pediatric Applications: Pediatric Musculoskeletal Ultrasound (Martinoli/Valle) -- Subject Index -- List of Contributors.
Keywords: Medicine; Radiology; Rheumatology; Orthopedics; Rehabilitation medicine; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Orthopedics; Rheumatology; Rehabilitation Medicine; Electronic books